2007
DOI: 10.1093/humrep/dem270
|View full text |Cite
|
Sign up to set email alerts
|

Are GnRH antagonists comparable to agonists for use in IVF?

Abstract: We believe that appropriate comparison of optimal GnRH agonist and antagonist regimens has not been performed yet. Currently available meta-analyses included all comparative studies between GnRH agonists and antagonists performed so far, including less than optimal GnRH antagonist regimens. After critical appraisal of the various studied GnRH antagonist regimens in terms of follicular development and IVF outcome, we postulate that early suppression of endogenous FSH results in optimal follicular development. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 67 publications
1
94
0
2
Order By: Relevance
“…This appears to be independent of whether a GnRH agonist or antagonist protocol is used [9,10]. For a number of years, a long mid-luteal GnRH agonist protocol for IVF was the standard of care, until research showed the feasibility of IVF with antagonist protocols.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This appears to be independent of whether a GnRH agonist or antagonist protocol is used [9,10]. For a number of years, a long mid-luteal GnRH agonist protocol for IVF was the standard of care, until research showed the feasibility of IVF with antagonist protocols.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment is on the one hand associated with an increased number of ovarian cysts, and on the other hand, with an increased prevalence of side effects, most notably, estrogenic deprivation symptoms. In contrast, GnRH antagonists cause immediate and rapid gonadotropin suppression, by competitive occupancy of the GnRH receptor, and thus intuitively make a more logical choice to use in IVF for the prevention premature LH surges, especially since they reduce the duration of treatment [10]. Therefore, GnRH antagonists could be administered at any time during the early or mid-follicular phase of a treatment cycle to prevent a premature LH surge [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that elevated endogenous FSH underline the synchronization of early antral follicles [10]. Follicular size heterogeneity has been shown to be negatively affecting the reproductive outcomes, GnRH agonists and OCP pills are used to abolish this discrepancy [11].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of GnRH antagonists seemed to open up a new way to more Bfriendly IVF^ [23]. Unlike indirect pituitary suppression induced by GnRH agonists, administration of GnRH antagonists causes immediate and dose-related suppression of gonadotropin release by competitive occupancy of GnRH receptors in the pituitary [24], which results in a much shorter duration of stimulation and absence of side effects caused by profound hypoestrogenemia [25,26]. A meta-analysis by AlInany et al demonstrated that the live birth rates between the use of GnRH antagonists and agonist protocols were comparable [27], but the majority of trials clearly support GnRH antagonists resulting in a significantly lower incidence (50 %) of OHSS compared with GnRH agonists [27][28][29].…”
Section: Freeze-all-why?mentioning
confidence: 99%